2010
DOI: 10.1039/c0an00529k
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive biochemical monitoring of physiological stress by Fourier transform infrared saliva spectroscopy

Abstract: Physical stress affects the immune system, activates the sympathetic (SNS) and parasympathetic (PNS) subsystems of autonomic nervous system (ANS), and increases the activity of the hypothalamic-pituitary-adrenal axis (HPA). The specific response of the major regulatory systems depends on the human functional state. Saliva is a unique diagnostic fluid, the composition of which immediately reflects the SNS, PNS, HPA and immune system response to stress. A new method of saliva biomarker determination by Attenuate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
64
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 53 publications
2
64
0
1
Order By: Relevance
“…Many studies demonstrated high sensitivity of FT-IR to analyze the skeletal muscle (Jerônimo et al, 2012), heart muscle (Cheheltani et al 2012), and some biological fluids, such as serum (Carvalho et al, 2014), urine (Khaskheli et al, 2013), and saliva (Khaustova et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Many studies demonstrated high sensitivity of FT-IR to analyze the skeletal muscle (Jerônimo et al, 2012), heart muscle (Cheheltani et al 2012), and some biological fluids, such as serum (Carvalho et al, 2014), urine (Khaskheli et al, 2013), and saliva (Khaustova et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The few studies that analyzed saliva by FT-IR have produced promising results with quantitative analysis of biochemical components and provided real-time information without the use of reagents (Khaustova et al, 2010;Perez-Guaita et al, 2012). This quantification, using the absorption bands of the vibrational modes of molecular radicals in the infrared Volume 31, Number 2, p. 116-124, 2015 region (4000-700 cm -1 ), identified specific bands for proteins, glucose, urea, secretory immunoglobulin A (sIgA), cortisol, and phosphate (Khaustova et al, 2009(Khaustova et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Miniature organ sizes and contact-free access to the transparent bottom of the chips might allow the use of strong inprocess research tools, such as, two-photon microscopy for tissue imaging, fluorescence ratio imaging for local interstitial pH measurement, 82 phosphorescence quenching microscopy for interstitial pO 2 , or infrared spectroscopy to detect physiological stresses. 83 Systems biology approaches for the identification of physiological performance, or adverse outcome pathways at stress overloads, might be applied on samples daily. 84 A few years ago, such a target seemed to be pure science fiction, but the unprecedented joint development programme between the NIH, DARPA and the FDA (http:// www.ncats.nih.gov/research/reengineering/tissue-chip/tissuechip.html), initiated in 2012, to develop ''human-on-a-chip'' systems combining ten human systems/organs on a single chip is a unique hallmark, indicating the translational impact of such concepts on the drug development pipeline.…”
Section: Prospective Improvements Of Existing Chip-based Liver Equivamentioning
confidence: 99%